Effects of bridging and V-sitting exercises on pain intensity and disability of patients with non-specific chronic low-back pain - Ojoawo, Adesola O.; Igbemo, Abdullai A.; Adeyemi, Timothy; Olaogun, Matthew OB. (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Exercises are important in the management of non-specific chronic low-back pain (NSCLBP). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The study compared the effects of bridging and V-sitting exercises on pain and disability of patients with NSCLBP. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. 34 patients with NSCLBP recruited for the study were allocated into V-sitting (VSG) and Bridging Exercise group (BEG) equally. Participants in VSG and BEG groups performed V-sitting and bridging exercises respectively for 10 seconds, three times in a week for three weeks under a supervision of one of the authors. Each participants underwent ten sessions per a treatment regimen. Pain intensity and disability were assessed at the pre-intervention, second and third weeks using verbal rating scale and Rolland Morris Low Back Pain Disability Questionnaire prospectively. Data were analyzed using descriptive and inferential statistics, alpha level was set at 0.05 <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. There was a significant reduction in the third week (P < 0.001) in both VSG and BEG group of pain intensity and disability comparing the pre intervention, second and third week values. There was a significant reduction in the 3rd week VSG’s pain intensity (F=27.34 P<0.001) and disability (F=14.96, P<0.001) compared with BEG. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. V-sitting and bridging exercises were effective in management of patients with NSCLP, but V-sitting seems more effective.